THE EFFECT OF ORGANIZATIONAL JUSTICE AND COMMITMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AMONG PUBLIC OFFICERS IN CILEUNYI DISTRICT, BANDUNG REGENCY - Ahmad Gumelar; Sindrawati Sindrawati; Muhammad Syukrullah Abdullah (SEAN Institute, 2023)
Extra-role behavior in a job is recognized as a form of positive behavior that supports the achievement of an organization. This article aims to examine how justice influences organizational citizenship behavior (OCB) directly or indirectly through organizational commitment. The unit of analysis in this study was employees who worked at the Cileunyi District Office, Bandung Regency. This study uses a census or saturated sample by taking respondents from all identified employees at the District Office. A total of 38 employees participated in this study by filling out the questionnaires that had been distributed. The research findings revealed that only 2 out of 5 paths of the relationship between variables were found to be significant. Procedural justice has an important influence on employee organizational commitment, while of the three determinants of OCB behavior, it was found that only organizational commitment affected OCB behavior. It can be concluded that the OCB among public officers can increase with the indirect effect of procedural justice through organizational commitment.